Analisis Kinerja Protokol Routing DSDV, DSR, ZRP, Dan AOMDV Dengan Menggunakan Standar IEEE 802.11 Dan 802.11p Pada Jaringan VANET (Vehicular Ad Hoc Network) - Sarah Atemalem Octaviana Toruan; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In recent years, wireless technology as a communication system has not been developed not only limited to the use of electronic devices, but also directed to the mobility of humans and vehicles that they use daily. This technological development used as a solution to solve problems in the public transportation system and accidents, because private vehicles, public transportation, and driving from one point to another have become an inseparable part of human daily life. The technology is called VANET (Vehicular Ad hoc Network). VANET as a method to overcome this problem must be supported by a routing protocol that has good performance for sending data. Some examples of these routing protocols include DSDV, DSR, AOMDV, and ZRP. The protocol must also be shipped with a supported network interface. The network interfaces that usually used on VANET are IEEE 802.11 and IEEE 802.11p standards. This study measure it using test parameters which are end-to-end delay, throughput, and packet delivery ratio. The results of the study show that the IEEE 802.11p standard has better performance rather than IEEE 802.11, produces better end-to-end delay values ​​with 40.99ms, 47.58ms, 49.52ms, and 5037.61 ms consecutively on the DSR, DSDV, AOMDV, and ZRP protocols. In addition, the resulting throughput value for the IEEE 802.11p standard is also greater than that of the IEEE 802.11 standard, with values ​​of 2029.05Kbps, 1556.67Kbps, 1541.88Kbps, and 0.71Kbps consecutively in the DSR, AOMDV, DSDV, and ZRP. On the performance of packet delivery ratio, the results obtained better values ​​for the DSDV and AOMDV protocols with 99.91% each on the IEEE 802.11 standard, and DSR and ZRP with values ​​of 99.97% and 68.75% on the IEEE standard 802.11p.